2013
DOI: 10.3109/09553002.2013.825061
|View full text |Cite
|
Sign up to set email alerts
|

Determining if low dose hyper-radiosensitivity (HRS) can be exploited to provide a therapeutic advantage: A cell line study in four glioblastoma multiforme (GBM) cell lines

Abstract: Ultra-fractionation (10 × 0.2 Gy) is an effective modality for killing glioma cell lines compared with standard 2 Gy dosing when multiple days of treatment are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Accumulating evidence suggests that it may have varied implications on radiotherapy practices. 130,131 While in vivo studies continue to provide insights into the potentially clinical implications of HRS/IRR in terms of exploitation of the response for a therapeutic benefit and implications for normal tissue reactions, no changes in current practices can be made until the underlying mechanism is fully understood. However, this would not be extensively discussed in here since the dose level is relatively higher than the dose levels ( 0.1 Gy or occupationally 0.2 Gy low LET radiation) effectively inducing hormesis and AR.…”
Section: The Elusively Multiple Mechanisms Underlying the Effects Of mentioning
confidence: 99%
“…Accumulating evidence suggests that it may have varied implications on radiotherapy practices. 130,131 While in vivo studies continue to provide insights into the potentially clinical implications of HRS/IRR in terms of exploitation of the response for a therapeutic benefit and implications for normal tissue reactions, no changes in current practices can be made until the underlying mechanism is fully understood. However, this would not be extensively discussed in here since the dose level is relatively higher than the dose levels ( 0.1 Gy or occupationally 0.2 Gy low LET radiation) effectively inducing hormesis and AR.…”
Section: The Elusively Multiple Mechanisms Underlying the Effects Of mentioning
confidence: 99%
“…However, some studies have reported that LDFRT at intervals of several hours does not enhance the cytotoxic effect [ 15 17 ]. On the other hand, other studies have reported that LDFRT at short time intervals (2 or 3 min) shows enhanced cytotoxic effects [ 18 20 ]. Depending on the unit dose and the total dose, LDFRT alone takes at least 15 min or more, even when short, 3-min intervals are used.…”
Section: Introductionmentioning
confidence: 98%
“…. (28) Notice that the difference between this matrix and the one in the previous subsection in (18) is the nonzero parameter θ in (28). As a check, this derivation should result in that of the last subsection when θ = 0.…”
Section: Radiation Exposure Time Too Short For Cell Progression But Smentioning
confidence: 69%